An Art Object on the Cross-Cultural Change: The Eleanor of Aquitaine Vase - Belova, Olga D. (Actual Problems of Theory and History of Art, 2017)
The main topic of the research is the so-called Eleanor of Aquitaine vase which is now housed in the collection of the Louvre. The provenance of the vase can be exactly traced back to the middle of the12th century, when it came to Paris as a wedding gift to Louis VII. It was later transferred to Abbot Suger and kept in the treasury of Saint-Denis, before it passed to the Louvre in 1793. The first purpose of our research is to try to clear the circumstances of the creation of the Eleanor of Aquitaine vase. Therefore, all the versions of possible identification of the vase’s presumable first owner Mitadolus with a particular historical figure, proposed in the scientific literature, should be studied carefully in order to consider the possibility of a meeting between this person and William of Aquitaine. The monument itself should be analyzed as one among many objects made of rock crystal or other comparable material of obviously similar origin (“from the East”). Secondly, very important goal of this work is to trace the history of the perception of the object in the 12th century France through the changes which happened to it: the physical one (mounting) and the spiritual one (a kind of religious change). Additionally, the article deals with the general problem of the existence and the “assimilation” of rock crystal items, which are presumably of Eastern (Islamic) origin, in the medieval Christian West, where they were highly valued during the Middle Ages.